2011
DOI: 10.1177/0042085911427739
|View full text |Cite
|
Sign up to set email alerts
|

Ogbu Revisited

Abstract: How African American girls cope and excel amidst the discriminations and inequities they experience within U.S. educational systems has not been widely discussed in the body of research about African Americans' schooling experiences. In this study, the researchers examined the applicability of Ogbu's cultural-ecological theory to the self-described school experiences of eight high-achieving African American high school girls. Using an inductive analysis of interviews, focus groups, journal, and field notes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 49 publications
1
59
0
Order By: Relevance
“…By doing so, scholars will take strides toward ensuring that their analysis respects these students' humanity. Although some of the scholars in this review noted reflecting on their identities through the use of analytical memos throughout their data collection (see Archer-Banks & Behar-Horenstein, 2012;Gholson & Martin, 2014;Nunn, 2018), majority of the scholars did not mention how they dealt with their own personal bias when studying these young women. A continuing process of reflection must become commonplace before, during, and after data collection when conducting research about Black girls and women.…”
Section: Engage In Continued Self-reflection On Personal Biasmentioning
confidence: 99%
“…By doing so, scholars will take strides toward ensuring that their analysis respects these students' humanity. Although some of the scholars in this review noted reflecting on their identities through the use of analytical memos throughout their data collection (see Archer-Banks & Behar-Horenstein, 2012;Gholson & Martin, 2014;Nunn, 2018), majority of the scholars did not mention how they dealt with their own personal bias when studying these young women. A continuing process of reflection must become commonplace before, during, and after data collection when conducting research about Black girls and women.…”
Section: Engage In Continued Self-reflection On Personal Biasmentioning
confidence: 99%
“…For instance, Irvine's (1986) seminal study of race and gender treatment in the classroom demonstrated how Black girls are more likely to experience more subtle forms of biased treatment, such as being ignored, negative nonverbal interactions, and relegation to caretaking roles rather than leadership roles in the classroom. Increasingly, scholars are studying how Black girls are uniquely marginalized in educational contexts based on race and gender (Archer-Banks & Behar-Horenstein, 2012). Such a focus is relevant considering Black girls' disproportionately high rates of disciplinary infractions compared with girls from other racial/ethnic groups (Blake et al, 2011).…”
Section: Gender and School Context Differences In School Discriminatimentioning
confidence: 99%
“…Cunningham, Corprew, and Becker (2009) suggested that the latter part of the 20th century and the first part of the 21st century could be characterized as the era of family transformation and stress. The family form is more diverse and more populated by single-parent households, blended family units, interracial marriages, and what demographers refer to as the new "stepfamily systems", which are created by cohabitation (Archer-Banks, & Behar-Horenstein, 2012). The seminal works of Mistry, Vandewater, Huston, and McLoyd (2002) provided both longitudinal and cross-sectional studies that emphasized the impact that family environments have on the youth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The notable increase in academic success among African American students that come from African American, femaleheaded, single parent, households has occurred in the shadow of years of oppression, historical trauma, and differential treatment related to race, gender and income. The plight of youth living with single mothers on low-income,struggling to overcome barriers while striving to succeed is a critical issue facing the current social context (Archer-Banks, & Behar-Horenstein, 2012). Research on resilience has consistently shown that low levels of income and single parenting are two potent risk factors that tend to have adverse impacts on families and children (Bryant, & Center for Law and Social Policy, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation